Estimate the Air Conditioner Capacity - Junaedi Irwan, Wan Abdul Halim (2021)
The hot temperature in our country makes it difficult and quite impossible for us to relax comfortably, even when the ceiling fan is set to maximum speed. Even at night, the heat is still felt, making us feel uncomfortable and preventing us from sleeping properly. As a result, installing an air conditioner in the bedroom and living room is the best solution for providing comfort to the entire family.